Central composite design aided optimization and validation of developed an eco-friendly HPLC method for the quantification of Lenalidomide loaded mesoporous silica nanoparticles - Ashutosh Gupta, Rachana S. P, Sudheer Moorkoth, Namdev Dhas (Journal of Applied Pharmaceutical Science, 2024)
Lenalidomide (LND) was encapsulated within mesoporous silica nanoparticles (MSNs), and we developed a reverse-phase (RP)-HPLC analytical method to quantitate the LND content in the formulation. Through a multivariate Central composite design (CCD), we systematically optimized key chromatographic parameters, including the flow rate, sample injection volume, and organic phase ratio. We evaluated the responses of retention time, peak area, and theoretical plate. Our enhanced chromatographic approach employed a Spherisorb ODS C18 column. To investigate the suitableness of the mobile phase for isocratic elution, we adhered to International Conference on Harmonisation Q2(R1) standards. Suggesting the optimality of a methanol and ammonium acetate buffer combination (pH 5.5, adjusted with 1% v/v glacial acetic acid and ammonia solution). This validated RP-HPLC analytical method exhibited specificity for LND even in the presence of the matrix of MSNs. The fabricated MSNs were confirmed by evaluating the surface morphology of the formulation. We successfully applied the developed RP-HPLC method to quantify the amount of LND entrapped and to determine the drug loaded in the MSNs formulation. The % EE for LND in MSNs was found to be 76.66% and % DL for LND in MSNs was found to be 1 4.00%, respectively. The novelty of the Design of expert-based method development is that it reduces the number of trials, thereby reducing solvent wastage and is environmentally friendly, scoring eight green, six yellow, and one red.
Keywords: Central Composite design, mesoporous silica nanoparticles, HPLC, Design of expert, nanoformulation